Real-time indoor air quality monitoring association with humidity, temperature, and carbon monoxide level in the residential environment / Mahanijah Md Kamal, Ahmad Syahir Sazali and Suzi Seroja Sarnin - Md Kamal, Mahanijah; Sazali, Ahmad Syahir; Sarnin, Suzi Seroja (Universiti Teknologi MARA, 2021)
Indoor Air Quality (IAQ) is the air quality in or around a building that can affect the comfort and health of building occupants. Polluted air contains toxic gases emitted by industry, vehicle emissions, and increased concentrations of harmful gases and particles in the atmosphere. The use of IoT can monitor IAQ reading levels and update IAQ real-time information parameters at different locations in the residential environment for the comfort and health of the occupants. The focus of this work is to measure the level of carbon monoxide (CO) as well as other important parameters such as temperature and relative humidity (RH) as recommended by ASHRAE 55-1992 and MS:1525. The developed system was built using NodeMCU as a microcontroller, MQ-7 to measure CO levels, and DHT22 sensor to measure the humidity and temperature levels. The experiment was conducted in a residential building located in Paya Jaras Tengah, Sungai Buloh, Selangor. The developed system was measured in three different locations, namely the living room, kitchen, and bedroom. In the morning, as the RH increased, the temperature also increased. Since the living room is located nearby the main road, the CO reading was higher than the other two locations, in which the highest value of 12 ppm was recorded. The results obtained showed that the system works well and can record the readings of RH, temperature, and CO level in the residential environment. Therefore, a reliable system can be developed to help the residential occupants monitor the level of IAQ in the house.